Global trends in dementia care research in the context of COVID-19: bibliometric analysis - Gómez-Galán, Rafael; Denche-Zamorano, Ángel; Mendoza-Muñoz, Maria; Pereira-Payo, Damián; Barrios-Fernández, Sabina; Muñoz-Bermejo, Laura (Frontiers in Medicine, 2024)
Alzheimer’s disease is the most common type of dementia, producing a deterioration in the activities of daily living which can lead to the need for care provision. COVID-19 impacted their quality of life and in this care delivery. This study aimed to analyse most productive and prominent authors, the journals and countries with the highest number of publications, the most cited documents and the most used keywords. Publications were retrieved from journals indexed in the Main Collection of the Web of Science (WoS) and analysed using the traditional laws of bibliometrics. A total of 376 documents were found. The WoS categories with the highest number of publications accumulated were “Geriatric Gerontology” and “Gerontology.” Clarissa Giebel was the most productive (23 papers) and most cited (with 569 citations) co-author. The Journal of Alzheimer’s Disease (21 papers) published the most number of documents. The manuscript “2021 Alzheimer’s Disease Facts and Figures” was the most cited. Four thematic clusters related to mental health, telemedicine, care and well-being were found among the authors’ keywords. Research networks exist worldwide, with the United States of America and England leading the scientific output. These results may be of interest to researchers, publishers and professionals interested in this subject, as they provide current information on publications related to this topic.